(untitled) (Research, Society and Development, 2025)
The work of teachers from early childhood education to higher education daily implies emotional suffering, which, if prolonged, can trigger psychological and/or physical pathologies. Thus, considering this problem, this article aimed to map in the scientific literature the emotional sufferings involved in teaching work manifested by teachers. This is a narrative literature review carried out in the Virtual Health Library (VHL) using two Health Sciences Descriptors (DeCS). The search located 86 scientific articles, and after reading the title and abstract, eight were included as a corpus of analysis. For analysis, a detailed reading was carried out, as well as a critical analysis of the texts, with the extraction of the following data: authors and year, article title, and the emotional sufferings manifested by teachers. The results showed that teachers frequently manifested emotional sufferings, regardless of the level of education they taught, encompassing early childhood education, elementary school, and higher education. In general, the sufferings ranged from stress, frustration, exhaustion, overload, and emotional wear. In conclusion, teachers from early childhood education, elementary school, and even higher education manifested emotional sufferings involved in teaching work. And considering that emotional suffering causes risks to the subject’s health, these results, which highlighted sufferings exposed by education professionals, can be used as indicators of vulnerability and illness, due to their potential to evolve into pathological physical and psychological symptoms, as occurs, for example, in Burnout Syndrome.